The Important Role of Emotional Intelligence in Supporting Auditor Performance - Wahyu Maulid Adha; Darman Syarif (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to examine and determine the effect of role conflict, role ambiguity, and role overload on the performance of auditors with emotional intelligence as a moderating variable at the Inspectorate of West Sulawesi Province. The population in this study includes the total number of auditors in the Inspectorate of West Sulawesi Province, as many as 49 auditors. In this study, the sample was taken using a census sampling technique in which the researcher took all pieces in the population. The data in this study used primary data collected by distributing questionnaires to all respondents. The statistical method used to test the hypothesis is to use multiple correlations with the help of SmartPLS software; after all the data in this study is collected, then data analysis is carried out consisting of descriptive statistical analysis, measurement model tests, or outer models consisting of (convergent validity), discriminant validity, composite reliability) and structural model tests or inner models were evaluated using R-square for the dependent construct and direct and indirect hypothesis testing. The results showed that role conflict, role ambiguity, and role overload negatively and significantly affected auditor performance. Meanwhile, emotional intelligence can moderate the relationship between role conflict, role ambiguity, and role overload on auditor performance.